Aging deformation resistance of nanoclaymodified stone mastic asphalt mixture - Mahdi, Lamya M.J (2015)
Many modifiers have been used to modify bitumen such as fiber, polymer, and filler which cost the road authorities a lot of money in addition to their side effects on the environment and their limited advantage. Aging have limited the service life of pavement and accelerated its premature failures. The problem of asphalt aging still exists in spite of the extensive use of the above mentioned modifiers. Montmorillonite nanoclay is one of the hybrid materials having a favored layer structure distinguish it from other materials in ability to disperse on a nanometer scale. It is a natural source material with a relatively low cost and more importantly environmentally friendly. The successfully intercalation chemistry of the layered silicates with polymers has been widely studied for a long time, and properties such as thermal, mechanical showed superior enhancement. Based on these findings, this study presents a laboratory investigation into the performance of asphalt binder and Stone Mastic Asphalt mixture modified with different type and concentration of nanoclay. The Rolling Thin Film Oven method was used to simulate the short term aging of the base and nanoclay modified asphalt binder, while the Stone Mastic Asphalt mixture was aged according to the asphalt mixture specification. The Dynamic Shear Rheometer was performed to characterize the rheological properties of asphalt binder at different temperatures and frequencies. The effect of nanoclay on the performance of the Stone Mastic Asphalt mixture was also investigated by means of the Indirect Tension Test and the Repeated Load Axial Test. The microscopic images indicated a homogenous dispersion of the layered silicate in asphalt medium while the spectroscopic technique showed the incorporation of the nanoclay in the asphalt binder matrix via new functional groups. Nanoclay was found to have a significant influence on asphalt binder and mixture properties. The higher nanoclay concentration showed better performance. The asphalt binder physical, rheological properties and rutting resistance were positively improved after the addition of nanoclay. The permanent deformation resistance of the Stone Mastic Asphalt mixture was found to be enhanced due to the stiffening effect of the nanoclay. Meanwhile,inconsistent trend was observed among the concentrations and types of nanoclay especially with permanent deformation test results, however, both of nanoclay types showed remarkable improvement as compared with the control mixture. The reason can be contributed to the complicated asphalt mixture failure mechanism since different variables having heterogeneous characters contributed in construction the Stone Mastic Asphalt mixture while using very close nanoclay concentration from each others can be a another reason. The short term aging resistance of modified binder was found to be improved which indicated the ability of layered nanoclay to act as a barrier that restricted and delayed the penetration of oxygen and played an important role to reduce the volatilization of the bitumen’s oily components and as consequence improved the asphalt binder resistance to rutting while enhanced the engineering properties of SMA mixtures as providing resistance against permanent deformation.